Probing the LSND mass scale and four neutrino scenarios with a neutrino telescope - Nunokawa, H. [UNESP]; Peres, O. L G; Zukanovich Funchal, R. (Elsevier, 2003)
We show in this Letter that the observation of the angular distribution of upward-going muons and cascade events induced by atmospheric neutrinos at the TeV energy scale which can be performed by a kilometer-scale neutrino telescope, such as the IceCube detector, can be used to probe a large neutrino mass splitting, |Δm 2| ∼ (0.5-2.0) eV 2, implied by the LSND experiment and discriminate among four neutrino mass schemes. This is due to the fact that such a large mass scale can promote non-negligible v μ → v e, v τ/v μ → v e, v τ conversions at these energies by the MSW effect as well as vacuum oscillation, unlike what is expected if all the neutrino mass splittings are small. © 2003 Elsevier Science B.V. All rights reserved.
Keywords: atmosphere; atomic particle; energy; mass; oscillation; physics; vacuum